LGBT health and nursing curriculum: vision of future nurses (Research, Society and Development, 2020)
Objective: to analyze the approach of the health issue of the LGBT population at a nursing college. Specific: to identify, in the course menus, the health theme of the LGBT population and describe, from the perspective of the undergraduate students, the approach of the theme in the classroom. Methodology: a mixed approach survey, using a form to analyze the syllabus of the curriculum subjects and, for the 29 undergraduate students from the last period of a public Nursing Faculty in the state of Rio de Janeiro, a questionnaire of sociodemographic issues was applied, and an interview was conducted half structured. Results: the analysis of the menus showed the presence of the theme in two mental health disciplines. The interviews demonstrated the superficial approach of the subject in the disciplines of child health, women's health and ethics, but without mention in their menus. It was found that the undergraduates valued the approach, pointing out that learning will favor the improvement of the current reality of lack of assistance in this population. Conclusion: the theme is approached superficially without a specific focus on the health of the LGBT population, even in the menus that contemplate the theme. In view of the above, it is suggested that the theme be assessed by the curricular commissions of the nursing faculties so that the subject can be approached transversally in the curriculum.